Image of sadness in the Lamentationof Al-Mutanabbi to His grandmother. (Damascus University Journal of arts and humanities sciences, 2023)
The research has presented an artistic analysis to the poem of Al-Mutanabbi’s when lamenting his grandmother. It also displayed the poet’s ability of art picturing and embodying the meanings of his poetry with harmonious artistic tools among themselves. He up-gathered some sub pictures to draw the whole major image within his poem. Then, he turned those major pictures into stanchion that strengthen the whole picture of lamenting in the poem. The research has shown three main images in the poem, as the poet's position on misfortunes, which was a hostile position, became evident in the image. Al-Mutanabbi saw life as an adversary that strikes him, and that he didn’t feel surprised from it’s deeds and attitude towards him. The research sheds light on the second main picture, showing the poet's grief for his grandmother, and revealing her value for him, as She was not only the woman who replaced his mother after she had died, but she was his educator, role model and guide in his life, and it is not far from saying that Al-Mutanabbi had his grandmother’s personality, ambition and temperament.The research highlighted in the analysis of the third picture the promise that was made between him and his grandmother. The research clarified how these three images were combined to present a picture of the great lamentation, which highlighted an accurate picture of the sad, angry, rebellious and aspiring Al-Mutanabbi.The research showed how the poet took the artistic image of all kinds as a means to clarify the meanings of lamentation. He used similes, metaphors, metaphors, innovative improvements, and the science of semantics, and used the conditional method to link causes with results, and these means became as various colors that decorated  the poem.
Keywords: Lament; Sorrow; The Covenant; Lamentation Image